Teaching Basic English in Higher Education: Effective EFL teaching through students’ lens. - Syahrir Syahrir; St. Hartina (Institut Agama Islam Negeri Palopo, 2022)
This study is quantitative-descriptive that applying a questionnaire to explore undergraduate students’ expectations and preferences in EFL teaching-learning activities. A convenience sample of 120 first-year university undergraduates at the start of their university life was used. They were enrolled in an Economic students degree course at an Indonesian university. The questionnaire focused on students' experiences and perceptions concerning teaching and learning strategies, students’ growth skills, the quality of English lecturers, and the students’ suggestions toward the Teaching-Learning Process. The data collected were calculated as percentages and discussed. The majority of the students preferred projects as effective teaching-learning strategies. Grammar was considered the most growth skill. Furthermore, good teaching skills and knowledgeable were reckoned as the most favorable qualities of an English teacher. They recommended more fun activities, fewer assignments, seek for other fun activities, and using online applications.